Forming-free, self-compliance WTe₂-based conductive bridge RAM with highly uniform multilevel switching for high-density memory - Abbas, Haider (2023)
In this work, forming-free and self-limited resistive switching characteristics are demonstrated in the transition-metal-chalcogenide-based conductive bridge RAM devices. Owing to the choice of a suitable solid electrolyte, the proposed WTe2-based devices present excellent switching characteristics offering highly desirable attributes such as high pulse endurance (> 2× 107 cycles) and stable data retention (10 years at 72°C). The devices also present excellent device-to-device and cycle-to-cycle uniformity which is highly desirable for the practical implementation of resistive random access memory (RRAM) devices in large crossbar arrays. The demonstration of robust and highly repeatable multilevel switching further provides multibit data storage capability for high-density memory.